Bombardiranje Maribora 1944–1945 kot del angloameriškega strateškega bombardiranja nemške vojaške industrije in prometnih zvez v luči primerjave slovenskih in angloameriških arhivskih virov - Prebilič, Vladimir (Studia Historica Slovenica, 2022)
Based on the study of archival sources in Archives of the Republic of Slovenia, The Regional Archives Maribor, National Archives and Records Administration (USA) and The National Archives (United Kingdom), the article brings to light new perspective on strategic significance of Maribor, a city through which ran an important railway connection between Germany and the Italian front, and its war industry – the Factory of Air Motors in Tezno. Consequently, the city’s aircraft industry and railway infrastructure became frequent targets of both strategic and tactical bombing. This article presents new discoveries and theoretical views through the use and comparison of various archival sources and places them into military-strategic concept of warfare during the Second World War. Along with the testimonies of the participants in the then events, the article also significantly upgrades all so far published research.
Keywords: Bombardiranje; druga svetovna vojna; strateško bombardiranje; Svetovna vojna (1939-1945); Vojne izgube; Vojno letalstvo